Risk of Congenital Toxoplasmosis in Newborns from Mothers with Documented Infection: Experience from Two Referral Centres - Alice Bonetti; Agnese Comelli; Annacarla Chiesa; Vania Spinoni; Ambra Vola; Federico Prefumo; Adriana Valcamonico; Carlo Bonfanti; Silvio Caligaris; Lina Rachele Tomasoni; Fausto Baldanti; Valeria Meroni (Pathogens)
During pregnancy, primary Toxoplasma gondii infection can cause congenital toxoplasmosis (CT). We described the newborns’ outcomes from a multicentre cohort of mothers with seroconversion (SC) at different gestational ages. This retrospective observational study (from 2007 to 2018) was conducted in two Italian referral hospitals: Fondazione IRCCS Policlinico San Matteo in Pavia and Spedali Civili in Brescia. In total, 247 pregnant women were enrolled: seroconversions were enrolled: seroconversions documented as having occurred in the two months preceding pregnancy in 12 cases (4.9%; 95% CI 2.2–7.5%), and during pregnancy in 235 cases (95.1%; 95% CI 92.5–97.8%). SC is defined as the appearance of specific anti-Toxoplasma antibodies (IgM/IgG) during pregnancy in a previously seronegative woman. A total of 56 (22.5%; 95% CI 17.3–27.7%) newborns were lost to follow-up; thus, the outcome of 193 (77.5%; 95% CI 72.3–82.7%) newborns was analyzed. The overall transmission rate of T. gondii infection was 23.8% (95% CI 17.8–29.8%), 0% (95% CI 0.0–11.9%) among the 1st trimester SCs, 12.5% (95% CI 5.6–19.4%) among the 2nd trimester SCs, 53.8% (95% CI 41.7–66.0%) among the 3rd trimester ones. No CT were found in the group of periconceptional infection. Among the infected newborns, clinically manifest cases were 12 (26.1%; 95% CI 13.4–38.8%), including 1 case (2.2%; 95% CI 2.0–6.4%) of stillbirth and 11 symptomatic neonates (23.9%; 95% CI 11.6–36.2%). A total of 83 amniocentesis were performed (33.6%; 95% CI 27.7–39.5%), no complication was recorded and no false positive or false negative results were registered. The results are in line with the fetal risks reported in literature for T. gondii infection during pregnancy, even if at a lower percentage probably due to a prompt treatment.